1997
DOI: 10.1113/jphysiol.1997.sp021916
|View full text |Cite
|
Sign up to set email alerts
|

Activation of A2‐purinoceptors by adenosine stimulates L‐arginine transport (system y+) and nitric oxide synthesis in human fetal endothelial cells.

Abstract: 1. Human umbilical vein endothelial cells were challenged acutely with adenosine and its analogues to examine whether adenosine modulates L-arginine transport (system y+) and synthesis of nitric oxide (NO) and prostacyclin (PGJ2). 2. L-Arginine transport was stimulated by adenosine (10 /M, 2 min) and the A2-receptor agonist 2-p-2-carboxyethyl)phenethylamino-5'-N-ethylcarboxamidoadenosine (CGS-21680; 100 nM), but not by the A,-receptor agonist N6-cyclopentyladenosine (CPA).3. Activation of L-arginine transport … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
88
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(100 citation statements)
references
References 19 publications
12
88
0
Order By: Relevance
“…It is known that sildenafil augments the IS-limiting effect of statins (34), whereas selective cyclooxygenase-2 inhibitors (3, 10) and aspirin (7) attenuate it. Since Akt (5,11,12,18,19,27,30,35,38,50,53) and eNOS (2,5,13,23,52) activation plays an important role in statin protection from ischemia-reperfusion injury and since statins activate ecto-5-nucleotidase and increase tissue levels of adenosine (9,35,46), which in turn activates Akt (26) and eNOS (15,29,39,40,47), we asked whether ATV, which generates adenosine via ecto-5-nucleotidase activation (9,35,46), and DIP, which prevents the reuptake and degradation of adenosine (17,37), could have synergistic effects on eNOS activation and IS limitation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is known that sildenafil augments the IS-limiting effect of statins (34), whereas selective cyclooxygenase-2 inhibitors (3, 10) and aspirin (7) attenuate it. Since Akt (5,11,12,18,19,27,30,35,38,50,53) and eNOS (2,5,13,23,52) activation plays an important role in statin protection from ischemia-reperfusion injury and since statins activate ecto-5-nucleotidase and increase tissue levels of adenosine (9,35,46), which in turn activates Akt (26) and eNOS (15,29,39,40,47), we asked whether ATV, which generates adenosine via ecto-5-nucleotidase activation (9,35,46), and DIP, which prevents the reuptake and degradation of adenosine (17,37), could have synergistic effects on eNOS activation and IS limitation.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that statins activate phosphatidylinositol-3-kinase (5,12,19,50) with subsequent activation of both Akt (5,11,12,18,19,27,30,35,38,50,53) and ecto-5-nucleotidase, which generates adenosine (9,35,46). Both Akt (5, 18, 27) and adenosine (15,29,39,40,47) activate endothelial nitric oxide synthase (eNOS). eNOS activation is essential for this protective effect, since nonspecific nitric oxide synthase inhibitors blunt the IS-limiting effect of statins (6, 51) and since statins do not reduce IS in eNOS Ϫ/Ϫ mice (5, 23, 52).…”
mentioning
confidence: 99%
“…Adenosine and endothelium-derived NO and prostacyclin are important local mediators of vasodilatation. In several human vascular beds, adenosine A 2 receptors mediate vasodilatation in part through endothelium, possibly by releasing NO (Sobrevia et al, 1997;Li et al, 1998) and prostacyclin (Chiang et al, 1994;Donoso et al, 2005). Other studies, however, failed to demonstrate endothelium-dependent responses in the presence of adenosine (Sabouni et al, 1990;Tsai et al, 1996;Kemp and Cocks, 1999).…”
mentioning
confidence: 93%
“…Other studies, however, failed to demonstrate endothelium-dependent responses in the presence of adenosine (Sabouni et al, 1990;Tsai et al, 1996;Kemp and Cocks, 1999). Controversy also exists on the receptor subtype (A 2A or A 2B ) predominating on endothelial cells (Chiang et al, 1994;Iwamoto et al, 1994;Sobrevia et al, 1997;Li et al, 1998;Donoso et al, 2005). Since little is known about the adenosine receptor present on endothelial cells of HCC and the impairment of endothelium function may be one of the factors for the attenuation of adenosine receptor-mediated responses, we thought it would be interesting to explore adenosine-induced relaxation of HCC smooth muscle in control subjects after inhibiting endothelial production of NO and prostacyclin compared with patients with vasculogenic impotence exhibiting multiple risk factors for endothelial lesion (e.g., type II diabetes, hypercholesterolemia, hypertension, heavy smoking habits).…”
mentioning
confidence: 99%
“…Recently, it has been demonstrated that activation of the adenosine A 2A receptor can cause NO release in endothelial cells. 22,23 In addition, it has been reported that adenosine induces endothelial NOS (eNOS) activation in a Ca 2ϩ -insensitive manner that involves extracellular signalregulated kinase (ERK) 1 and 2 phosphorylation in human umbilical vein endothelial cells. 24 This raises the possibility that the cardiovascular modulatory effects of adenosine in the NTS might be mediated through activation of ERK1/2 and eNOS.…”
Section: Clinical Perspective P 780mentioning
confidence: 99%